Targeting TPX2 Suppresses the Tumorigenesis of Hepatocellular Carcinoma Cells Resulting in Arrested Mitotic Phase Progression and Increased Genomic Instability - Hsu, Chao-Wen (J Cancer, 2017)
Hepatocellular carcinoma (HCC) remains one of the most difficult cancers to treat, with chemotherapies being relatively ineffective. Therefore, a better knowledge of molecular hepatocarcinogenesis will provide opportunities for designing targeted therapies. TPX2 (targeting protein for Xklp2) is overexpressed as a consequence of oncogenic alterations and is likely to alter the proper regulation of chromosome segregation in cancer cells. Disrupting the machinery which is responsible for mitosis and chromosome instability in cancer cells can be one of the most successful strategies for cancer therapy. Therefore, we consider the targeting TPX2 could provide novel therapeutic strategies for cancer. In this study, increased TPX2 protein expression was present in 16 (42%) of 38 primary HCCs and was associated with advanced stage, distant metastatic HCCs and poor prognosis. Knockdown of TPX2 inhibited cancer cell growth and downregulation of cyclin A, cyclin E and CDK2 proteins. However, over-expressed EGFP-TPX2 protein enhanced the in vitro tumor spheroid formation and rescued the TPX2 depleted cell growth. Targeting TPX2 caused a rising impaired chromosomal instability resulting in multinuclearity, cell cycle progression arrest, apotosis, senescence and an increased polyploidy in cells. An image-cytometry analysis revealed cell cycle progression arrest after TPX2 inhibition. A correlation was observed between the downregulation of the protein levels of genes related to chromosomal segregation and spindle assembly checkpoint (securin, seprase, Aurora A, Aurora B, Cyclin B1, Cyclin B2, MPS1, BUB1, BUB3, MAD1 and MAD2) and increased cell ploidy, indicating mitotic progression failure and the loss of the balance of genomic instability. In vitro tumor spheroid assay and in vivo xenografts mouse model showed a therapeutic opportunity. Our findings indicate that targeting TPX2 lead to suppress tumorigenicity in liver cancer cells, suggesting that TPX2 is a potential target for anticancer therapy in HCC.